Assessing Autophagy in Microglia: A Two-Step Model to Determine Autophagosome Formation, Degradation, and Net Turnover - Plaza-Zabala, Ainhoa; Sierra-Torre, Virginia; Sierra, Amanda (Frontiers in Immunology, 2021)
Autophagy is a complex process that encompasses the enclosure of cytoplasmic debris or dysfunctional organelles in membranous vesicles, the autophagosomes, for their elimination in the lysosomes. Autophagy is increasingly recognized as a critical process in macrophages, including microglia, as it finely regulates innate immune functions such as inflammation. A gold-standard method to assess its induction is the analysis of the autophagic flux using as a surrogate the expression of the microtubule-associated light chain protein 3 conjugated to phosphatidylethanolamine (LC3-II) by Western blot, in the presence of lysosomal inhibitors. Therefore, the current definition of autophagy flux actually puts the focus on the degradation stage of autophagy. In contrast, the most important autophagy controlling genes that have been identified in the last few years in fact target early stages of autophagosome formation. From a biological standpoint is therefore conceivable that autophagosome formation and degradation are independently regulated and we argue that both stages need to be systematically analyzed. Here, we propose a simple two-step model to understand changes in autophagosome formation and degradation using data from conventional LC3-II Western blot, and test it using two models of autophagy modulation in cultured microglia: rapamycin and the ULK1/2 inhibitor, MRT68921. Our two-step model will help to unravel the effect of genetic, pharmacological, and environmental manipulations on both formation and degradation of autophagosomes, contributing to dissect out the role of autophagy in physiology and pathology in microglia as well as other cell types.